Advancing Lignocellulosic Biorefineries through Co-Production of Hemicellulosic Biopolymers and Bioenergy - Mihiretu, Gezahegn Teklu (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.